2010
DOI: 10.1007/s00125-010-1783-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in short- and long-term cardiovascular risk of incident diabetes and incident myocardial infarction—a nationwide study

Abstract: Aims/hypothesis We assessed secular trends of cardiovascular outcomes following first diagnosis of myocardial infarction (MI) or diabetes in an unselected population. Methods All Danish residents aged ≥30 years without prior diabetes or MI were identified by individual-level linkage of nationwide registers. Individuals hospitalised with MI or claiming a first-time prescription for a glucose-lowering medication (GLM) during the period from 1997 to 2006 were included. Analyses were by Poisson regression models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 31 publications
3
42
0
2
Order By: Relevance
“…Thus, focus on CVD prevention in RA patients should not be reserved for any particular age group. The overall increased risk of CVD in DM patients, as well as the finding that DM confers a higher risk of CVD in women than in men, are well-documented in the literature, including studies from our group indicating that the CVD risk in diabetes patients requiring glucose-lowering therapy is comparable to the risk in non-DM subjects with prior MI 24 27 29. In view of the aggressive approach to primary CVD prevention in DM patients, the recent results from van Halm and coworkers, showing equal prevalence of CVD in two Dutch RA and DM cohorts, have fuelled the discussion on the necessity for more aggressive CVD prevention in RA patients 19.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Thus, focus on CVD prevention in RA patients should not be reserved for any particular age group. The overall increased risk of CVD in DM patients, as well as the finding that DM confers a higher risk of CVD in women than in men, are well-documented in the literature, including studies from our group indicating that the CVD risk in diabetes patients requiring glucose-lowering therapy is comparable to the risk in non-DM subjects with prior MI 24 27 29. In view of the aggressive approach to primary CVD prevention in DM patients, the recent results from van Halm and coworkers, showing equal prevalence of CVD in two Dutch RA and DM cohorts, have fuelled the discussion on the necessity for more aggressive CVD prevention in RA patients 19.…”
Section: Discussionsupporting
confidence: 59%
“…The last of either the prescription date or the date of diagnosis was used as the index date for RA time at risk. Subjects were considered as DM patients at the initiation of pharmacological treatment with oral glucose-lowering drugs or insulin analogues (ACT code A10) 24. If patients developed both conditions (RA+DM) during the follow-up period, the date of diagnosis of the second of the two conditions denoted the start of time at risk in the models, which included a RA+DM group.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with type 2 diabetes have a well-established high risk of cardiovascular disease and mortality, compared with the general population [1][2][3][4]. For a long while it was anticipated that tight normalisation of blood glucose would reduce cardiovascular and all-cause mortality, but recently this dogma has been questioned after some studies reported low normal HbA 1c , as well as high HbA 1c , levels to be associated with an increased risk of mortality (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The primary end point was the development of DM needing pharmacotherapy, which was defined by initiation of glucose-lowering drugs (A10), identified by claimed prescriptions from pharmacies, as done previously (19,21,22). Glucose-lowering drugs are not available over the counter in Denmark.…”
Section: Methodsmentioning
confidence: 99%